THE NATURE OF PSYCHOPHYSIOLOGICAL CHANGES DURING ADOLESCENCE - Isakova Mu'azam Tulkinovna (World Scientific Research Journal, 2025)
Abstract. Adolescence is a critical period marked by significant physiological and psychological changes, including hormonal, neural, and behavioral transformations. This article explores the complex relationship between these physiological changes and their psychological manifestations, focusing on how hormonal shifts, neural development, and stress responses influence emotional regulation, personality formation, and social behavior in adolescents. By analyzing data from 150 adolescents, the study provides insights into how these biological processes shape emotional and behavioral outcomes during this developmental stage. The findings emphasize the importance of emotional regulation and stress management in supporting healthy adolescent development.